Prawne aspekty refundacji sprzętu ortopedycznego = Legal aspects of orthopaedic equipment, refunds - Zniszczol, Paweł; Gryczka, Monika; Kropkowska, Patrycja; Kaźmierczak, Urszula; Radzimińska, Agnieszka; Weber‑Rajek, Magdalena; Strojek, Katarzyna; Goch, Aleksander (Journal of Education, Health and Sport, 2015)
Zniszczol Paweł, Gryczka Monika, Kropkowska Patrycja, Kaźmierczak Urszula, Radzimińska Agnieszka, Weber‑Rajek Magdalena, Strojek Katarzyna, Goch Aleksander. Prawne aspekty refundacji sprzętu ortopedycznego = Legal aspects of orthopaedic equipment, refunds. Journal of Education, Health and Sport. 2015;5(5):516-530. ISSN 2391-8306. DOI10.5281/zenodo.30567 http://dx.doi.org/10.5281/zenodo.30567 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A516-530 https://pbn.nauka.gov.pl/works/620763 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 06.09.2015. Prawne aspekty refundacji sprzętu ortopedycznego Legal aspects of orthopaedic equipment, refunds Paweł Zniszczol1, Monika Gryczka2, Patrycja Kropkowska1, Urszula Kaźmierczak¹, Agnieszka Radzimińska¹, Magdalena Weber-Rajek1, Katarzyna Strojek¹, Aleksander Goch¹ 1 Katedra Fizjoterapii , Zakład Kinezyterapii i Masażu Leczniczego, Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy 2 Instytut Prawa, Administracji i Zarządzania, Wydział Administracji i Nauk Społecznych, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: refundacja, sprzęt ortopedyczny, Narodowy Fundusz Zdrowia, PFRON, prawne aspekty, niepełnosprawność, orzecznictwo. Key words: refund, orthopedic equipment, National Health Fund, PFRON, legal aspects, disability, case-law. Streszczenie: Osobą niepełnosprawną można stać się bardzo łatwy sposób, wystarczy moment – chwila nieuwagi i życie osoby może zmienić się diametralnie. Z osoby cieszącej się pełnią zdrowia, radością życia, można stać się osobom niepełnosprawną, która niejednokrotnie będzie potrzebować pomocy innych. Może być uzależniona od innych, czy wymagać stałej opieki. W powrocie do „normalnego życia” pomocne będą: rehabilitacja, wsparcie społeczne i psychologiczne, a także środki ortopedyczne i pomocnicze, które pozwolą na jak najlepsze, w stosunku do stanu zdrowia, funkcjonowanie osobie niepełnosprawnej w życiu codziennym, społecznym i kulturowym. Pomocne w tym procesie może być właśnie dofinansowanie ze środków: Narodowego Funduszu Zdrowia i Państwowego Funduszu Rehabilitacji Osób Niepełnosprawnych, z których możemy starać się o dofinansowanie na zakup sprzętów, które ułatwią nam życie, będąc osobą niepełnosprawną. Abstract: A disabled person can become a very easy way, just a moment - a moment of inattention and can change a person's life forever. With people enjoying the fullness of health, joy of life, you become a person with a disability who often will need the help of others. It may be dependent on others or require constant care. In returning to "normal life" will be helpful: rehabilitation, social and psychological support, as well as orthopedic and auxiliary agents that allow for the best, in relation to health, functioning person with a disability in everyday life, society and culture. Helpful in this process can be precisely funding from: National Health Fund and the State Fund for Rehabilitation of Persons with Disabilities, from which we can apply for funding to purchase equipment that will facilitate our lives, being a disabled person.